Healing and Therapeutic Trajectories Among the Spirit Mediums of the Brazilian Vale do Amanhecer - Pierini, Emily (International journal of Latin American religions, 2018)
The temples of the Vale do Amanhecer (Valley of the Dawn) in Brazil and across the world are intended as spiritual emergency units where mediums and their spirit guides provide patients with free assistance for health, relational, spiritual, and material matters concerning the person's wellbeing. The therapeutic practice is known as disobsessive healing and involves the release of causal spiritual agents considered to be affecting the person's wellbeing. This paper discusses the Vale do Amanhecer's etiology of illness and how mediums understand disobsessive healing as a complementary epistemology of healing, discerning spiritual and pathological experiences. Then, it examines how patients may draw their therapeutic trajectories across biomedical and spiritual contexts, sometimes developing mediumship as part of their therapeutic process. Approaching these therapeutic practices from the standpoint of affect and bodily experience may undermine the prominence of belief in the study of non-biomedical approaches to healing, shedding light upon the relational, embodied, and lived-through dimensions of the notions involved in the therapeutic process.